Complex Profiles of Cerebrovascular Disease Pathologies in the Aging Brain and Their Relationship With Cognitive Decline. Issue 1 (January 2022) - Lamar, Melissa; Leurgans, Sue; Kapasi, Alifiya; Barnes, Lisa L.; Boyle, Patricia A.; Bennett, David A.; Arfanakis, Konstantinos; Schneider, Julie A.
Abstract : Background and Purpose: Cerebrovascular disease (CVD) pathologies including vessel disease (atherosclerosis, arteriolosclerosis, and cerebral amyloid angiopathy) and tissue injury (macroinfarcts and microinfarcts) each contribute to Alzheimer and other forms of dementia. CVD is often a complex mix of neuropathologies, with little known about the frequencies of differing combinations or their associations with cognition. Methods: We investigated 32 possible CVD combinations (3 types of vessel disease and 2 types of tissue injury) using autopsy data from 1474 decedents (≈88 years at death; 65% female) of Rush Alzheimer's Disease Center studies. We determined frequencies of all 32 CVD combinations and their relationships with global and domain-specific cognitive decline using mixed-effect models adjusted for demographics, neuropathologies, time before death, and interactions of these variables with time. Results: Of the 1184 decedents with CVD neuropathology (80% of the total sample), 37% had a single CVD (67–148 decedents/group) while 63% had mixed CVD profiles (11–54 decedents/group). When considered as 2 distinct groups, the mixed CVD profile group (but not the single CVD profile group) showed a faster cognitive decline across all domains assessed compared with decedents without CVD neuropathology. Most mixed CVD profiles, especially those involving both atherosclerosis and arteriolosclerosis, showed faster cognitive decline than any single CVD profile considered alone; specific mixed CVD profiles differentially associated with individual cognitive domains. Conclusions: Mixed CVD, more common than single CVD, is associated with cognitive decline, and distinct mixed CVD profiles show domain-specific associations with cognitive decline. CVD is not monolithic but consists of heterogenous person-specific combinations with distinct contributions to cognitive decline. Abstract : Supplemental Digital Content is available in the text.